Those Good Gertrudes : A Social History of Women Teachers in America - Clifford, Geraldine Jonçich (Book collections on Project MUSE., 2014)
Those Good Gertrudes explores the professional, civic, and personal roles of women teachers. Its voice, themes, and findings build from the mostly unpublished writings of many women and their families, colleagues, and pupils. Geraldine J. Clifford studied personal history manuscripts in archives and consulted printed autobiographies, diaries, correspondence, oral histories, interviews--even film and fiction--to probe the multifaceted imagery that has surrounded teaching. This work stands alone: it is broad ranging, inclusive, and comparative. It surveys a long past where schoolteaching was essentially men's work, with women relegated to restricted niches such as teaching rudiments of the vernacular language to young children and socializing girls for traditional gender roles. Clifford documents and explains the emergence of women as the prototypical schoolteachers in the United States, a process apparent in the late colonial period and continuing through the nineteenth century, when they became the majority of American public and private schoolteachers. She finds that this trend continues in the twenty-first century, despite the diversion of women to competing professions, a precipitous reduction in the number of Roman Catholic nuns, and repeated efforts and incentives to recruit and retain male teachers. Cross-national comparisons suggest that America's early reliance on women teachers quickened and extended the reach of schools across the nation's social classes, religious and ethnic groupings, and cultural and physical landscapes. The capstone of Clifford's distinguished career and the definitive book on women teachers in America, Those Good Gertrudes will engage scholars in the history of education and women's history, teachers past, present, and future, and readers with vivid memories of their own teachers.